The Effectiveness of Image-Based Learning Media in Enhancing Student Motivation in Geography Classrooms: A Quasi-Experimental Study - Putri Wahyuni (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2026)
This study aims to examine the effect of image-based learning media on students' learning motivation in Geography at SMA Negeri 4 Pekanbaru. A quantitative approach with a quasi-experimental design was used. The population consisted of 229 grade XI IPS students, with a sample of 77 students selected using a random sampling method. Data were collected using a validated 24-item questionnaire that demonstrated high reliability (Cronbach's Alpha ≥ 0.8) to measure students' learning motivation before and after the intervention. The intervention involved the use of image-based learning media during Geography lessons, where students were presented with visual representations of concepts and phenomena to facilitate understanding and engagement. Descriptive and inferential analyses, including independent t-tests, were conducted to evaluate the results. The findings indicated that the use of image-based media significantly improved students' motivation, with a post-test mean difference of 12.28 (t = 6.811, p = 0.000) and an effect size of 1.55, indicating a strong practical impact. In conclusion, integrating image-based media into Geography teaching effectively increases student motivation, particularly in understanding complex topics such as natural disasters. Further research is recommended to explore the combination of image-based media with other active learning methods and to examine its impact on cognitive and critical thinking skills at various school levels.